2014
DOI: 10.1080/02626667.2013.866709
|View full text |Cite
|
Sign up to set email alerts
|

Can satellite land surface temperature data be used similarly to river discharge measurements for distributed hydrological model calibration?

Abstract: A new methodology is proposed for the calibration of distributed hydrological models at the basin scale by constraining an internal model variable using satellite data of land surface temperature (LST). The model algorithm solves the system of energy and mass balances in terms of a representative equilibrium temperature that governs the fluxes of energy and mass over the basin domain. This equilibrium surface temperature, which is a critical model state variable, is compared to operational satellite LST, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…In that study, they found that the consideration of spatially averaged T s , besides streamflow, improved monthly evapotranspiration predictions by up to 20%. Similar efforts were undertaken by Corbari et al (2010Corbari et al ( , 2015 and Silvestro et al (2013Silvestro et al ( , 2015.…”
Section: /2017wr021346mentioning
confidence: 83%
See 1 more Smart Citation
“…In that study, they found that the consideration of spatially averaged T s , besides streamflow, improved monthly evapotranspiration predictions by up to 20%. Similar efforts were undertaken by Corbari et al (2010Corbari et al ( , 2015 and Silvestro et al (2013Silvestro et al ( , 2015.…”
Section: /2017wr021346mentioning
confidence: 83%
“…It should be noted that the land surface models employed in those studies explicitly solved the energy balance and thus inherently estimated the land surface temperature Their authors, however, did not specifically focus on the spatial distribution of T s . Consequently, models were either calibrated using basin averaged T s (Silvestro et al, 2013(Silvestro et al, , 2015 or compared observations and simulations using standard error metrics such as bias or root mean squared error (Corbari et al, 2010(Corbari et al, , 2015. Reichle et al (2010), Stisen et al (2011), andKoch et al (2015) on the other hand suggested using biasinsensitive metrics, which only consider the spatial patterns of land surface temperature.…”
Section: /2017wr021346mentioning
confidence: 99%
“…Models for projecting runoff response to vegetation changes are often constrained by discharge alone [Corbari et al, 2015]. However, there has also been a concerted effort for continued field studies and increased observational data to adequately support modeling efforts [Dunne, 1983;Grayson et al, 1992;Silberstein, 2006;Burt and McDonnell, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, satellite remote sensing comes into play as an independent data source with the required spatial resolution and coverage for many catchment-scale applications. Satellite imagery has been used for estimation of numerous states and fluxes of interest to hydrological modeling, such as snow cover (Immerzeel et al, 2009), groundwater storage change (Chen et al, 2016;Rodell et al, 2009;Sutanudjaja et al, 2013;Richey et al, 2015), soil moisture (SM; Wanders et al, 2014), vegetation water content (Mendiguren et al, 2015), land surface temperature (LST; Corbari et al, 2015) or actual evapotranspiration (ET; Guzinski et al, 2015). The conversions of the remotely sensed signal to hydrological variables are far from trivial and usually require in situ measurements and observations for model evaluation.…”
Section: G Mendiguren Et Al: a Remote-sensing-based Diagnostic Apprmentioning
confidence: 99%